Estimating the potential of beekeeping to alleviate household poverty in rural Uganda - Amulen, Deborah R.; D’Haese, Marijke; D’Haene, Eline; Okwee Acai, James; Agea, Jacob G.; Smagghe, Guy; Cross, Paul (PLoS ONE, 2019)
Robust evidence underpinning the role of beekeeping in poverty alleviation is currently lacking. This study estimated the production potential for beekeepers in Northern Uganda by quantifying current production assets (equipment and knowledge) and impact on rural income streams range of proposed interventions. Intervention scenarios evaluated the economic benefits to be derived from different hive types combined with year-round provision of a nectar source (Calliandra calothyrsus) planted at varying density. Findings show that the type and number of beehive combinations used influenced the amount of revenue streams generated by the beekeepers. Addition of 20 log hives increased incomes 10 times, 20 KTBs increased revenues 16 times and Langstroth 18 times. Adding Calliandra trees as a forage source to the baseline scenario yielded revenues up to 17.6 times higher than the baseline. Implying that good management plus the introduction of a reliable nectar source, to off-set dry season challenges (absconding), could improve beekeeping productivity in Northern Uganda. Further research is required to validate in situ the impact of modelled scenarios on both honey yield and other ecosystem service benefits.
Keywords: Beekeeping; poverty alleviation; Northern Uganda